Protocol for evaluating and implementing a pragmatic value-based healthcare management model for patients with inflammatory arthritis: a Danish population-based regional cohort and qualitative implementation study. Issue 10 (23rd October 2018) - Jørgensen, Tanja Schjødt; Lykkegaard, Jens Jørgen; Hansen, Annette; Schrøder, Heidi Morsø; Stampe, Betina; Sweeney, Anne-Marie Tetsche; Appel Esbensen, Bente; Bech, Bianca; Christensen, Katja; Friis-Mikkelsen, Ellen; Røgind, Henrik; Lundbak, Tine; et al.
Abstract : Introduction: The provision of healthcare for patients with inflammatory arthritis occurs in the context of somewhat conflicting targets, values and drivers. Therefore, there is a need for introducing 'value-based healthcare' defined as the value of patient relevant health outcomes in relation to costs. This term is a central part of tomorrow's healthcare sector, especially for rheumatic diseases, yet the transition is a huge challenge, as it will impact the development, delivery and assessment of healthcare. Aims: The aim of this study is to compare medical and patient evaluated impact of the traditional settlement and financing production (DAGS) controlled healthcare setting with a value-based and patient-centred adjunctive to standard care. Methods and analysis: Patients with inflammatory arthritis receiving treatment in routine care at the outpatient clinics in the Capital Region of Denmark will prospectively and consecutively be enrolled in a Non-Intervention-Study framework providing a pragmatic value-based management model. A Danish reference cohort, used for comparison will be collected as part of routine clinical care. The enrolment period will be from 1 June 2018 until 31December 2023. Baseline and follow-up visits will be according to routine clinical care. Registry data will be obtained directly from patients and include personal, clinical and outcomes information. The study results will be reported in accordance with the STROBE statement. Ethics and dissemination: The study has been notified to the Danish Data Protection Agency and granted authorisation for the period June 2018 to January 2025 (pending). Informed consent will be obtained from all patients before enrolment in the study. The study is approved by the ethics committee, Capital Region of Denmark (H-18013158). Results of the study will be disseminated through publication in international peer-reviewed journals.